Development of medical science - Finley, George William (My University, 1896)
Introduction: In treating this subject we propose to divide it into three main divisions which are more and less uniform throughout. The first of these will take us from earliest time to the decline of Roman Literature. The second from the decline of Roman literature to the revival of learning. The third from the revival of learning to the present day. The practice of medicine in its earliest form must have started very soon after man made his appearance upon the earth. He could not have existed long without becoming aware of the fact that he was subjected to certain ailments and that certain condition and foods helped him back to health. Thus he would learn that certain pains were helped by a vaccination at the contents of the intestines, and that these pains were caused by certain instances. So also he would soon learn to bind up a wound. However the mind of early man was so superstitious that he would naturally use very many things that were useless and even harmful.
Citation: Finley, George William. Development of medical science. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Roman literature; Learning; Present day; Medical science; Theses; Manuscripts (documents)